Twenty-first century tendencies: characters, confrontation and freedom in the us teleserial post-drama: Cultural hybridizations with Spanish-language dramatic culture - Orosa, Miguel A.; Galarza-Ligña, Viviana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The purpose of the ensuing research is to highlight the patterns of the transformations that have taken place in some of the most prestigious television series in the United States in terms of conflict, characters and the decomposition of the classic categories (freedom). Methodologically, the aim is to make an empirical analysis, within the framework of certain scientific models, that would address the current North American tele-serial post-drama and its antecedents in the dramatic culture so typical of the libertarian and anti-classical worldview that enriches the Spanish language.